REFORMASI BIROKRASI BELAJAR DARI UPAYA REFORMASI SUMBER DAYA MANUSIA APARATUR DI INDONESIA - Taufik Taufik (Jurnal Transformasi Administrasi, 2020)
The new paradigm in human resource management as an organizational asset has changed the way the government views continuous improvements through the grand design of bureaucratic reform. This study aims to explore bureaucratic reform in the human resources sector in Indonesia. This research uses a qualitative approach, with the type of research literature study. This study focuses on three reform agendas in the field of human resources, including the implementation of a merit system in open selection for high-ranking ASN positions, a performance appraisal system, and talent management. The results of the study found that in the implementation of the merit system in the open selection of high ranking ASN, several weaknesses were still found, such as expensive implementation costs, restrictions, took a long time, and there was still political intervention. Meanwhile, the ASN performance appraisal has undergone a change from the DP3 system to SKP, but in its implementation there is still an ASN mindset that considers SKP only as a formality. Meanwhile, talent management is a new program initiated by the government with the aim of producing competent, quality and competitive human resources. The success of bureaucratic reform is strongly influenced by the joint commitment between the leadership and staff to implement the reform agenda. Therefore, a joint commitment is needed in order to produce quality and productive human resources of the Indonesian apparatus.